(untitled) (Research, Society and Development, 2021)
This work was carried out to study the glycerin and cashew and castor oils inclusion as natural additives on fatty acid composition of perirenal fat, subcutaneous fat and muscle Longissimus thoracis of Purunã bulls finished in feedlot for 252 days. A total of 32 Purunã bulls (11-12 ± 2.0 months; 202.8 ± 14.4 kg) were finished in feedlot with 4 diets (n = 8): CONT – basal diet; VOIL – basal diet and inclusion of vegetable oils (3 g/animal/day); GLYC – basal diet and inclusion of glycerin (20.1% glycerin in DM basis); GLVO – basal diet and inclusion of glycerin (20.1% glycerin in DM basis) and vegetal oils (3 g/animal/day). Glycerin inclusion reduced SFA, MUFA and PUFA levels in the diets. Glycerin and vegetable oils inclusion in the diets of bulls finished in feedlot did not change (P > 0.05) lauric, myristic, palmitic, docosanoic, n-7-tetradecenoic, palmitoleic, n-11 trans-vaccenic, oleic, n-7 cis-vaccenic, cis-9, t11 – CLA, n-3 docosapentaenoic and n-3 docosahexaenoic fatty acids levels in perirenal fat, subcutaneous fat and Longissimus thoracis muscle of bulls finished in feedlot. However, glycerin inclusion in the diets increased (P < 0.05) pentadecanoic, margaric and n-9, cis-10 heptadecanoic fatty acids levels when compared of perirenal fat, subcutaneous fat and Longissimus thoracis muscle of bulls fed CONT and VOIL diets. On the other hand, glycerin inclusion decreased (P < 0.05) linoleic fatty acid in perirenal fat, subcutaneous fat and Longissimus thoracis muscle in comparison of CONT and VOIL diets. Glycerin and vegetables oils inclusion in the diets did not alter (P > 0.05) SFA and MUFA levels in perirenal fat from bulls fed four diets. The PUFA, n-6 and n-3 levels and PUFA:SFA and n-6:n-3 ratios were similar (P > 0.05) between perirenal fat of bulls fed CONT and VOIL diets and greater (P < 0.05) when compared of perirenal fat from bulls fed GLYC and GLVO diets. SFA, MUFA levels and n-6 and n-3 ratios were similar (P > 0.05) among all diets. PUFA and MUFA levels in fat subcutaneous and n-6:n3 ratio were similar (P > 0.05) between GLYC and GLVO diets, but greater than CONT and GLYC diets. Total fatty acids sum levels in Longissimus thoracis muscle were similar (P > 0.05) among bulls from all diets, except the lowest levels in bulls from GLYC and GLVO diets in comparison to CONT and VOIL diets. In conclusion glycerin inclusion in the diets modifies fatty acids in fat and muscle of bulls finished in feed-lot.